Growth performance and survival rate of spiny lobster Panulirus homarus (Linnaeus, 1758) with formulated feeding enriched by spinach extract - AMELIA SRIWAHYUNI LUBIS; EFRIZAL EFRIZAL; SYAIFULLAH SYAIFULLAH; RUSNAM RUSNAM; NURMIATI NURMIATI; ANINDA TIFANI PUARI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lubis AS, Efrizal, Syaifullah, Rusnam, Nurmiati, Puari AT. 2023. Growth performance and survival rate of spiny lobster Panulirus homarus (Linnaeus, 1758) with formulated feeding enriched by spinach extract. Biodiversitas 24: 6010-6016. In the context of spiny lobster Panulirus homarus (Linnaeus, 1758) aquaculture and marine conservation, assessing factors that influence growth and survival is critical. Spinach extract can be added as a feed additive to enhance the growth and survival rate of lobsters. This study aimed to analyze the effect of formulated feed enriched with spinach extract on spiny lobsters' growth and survival performance. A completely randomized design with five treatments and five replications: formulated feed with spinach extract 0 mg (Feed A1), 0.4 mg (Feed A2), 0.5 mg (Feed A3), 0.6 mg (Feed A4), and 0.7 mg (Feed A5) were used. The result showed that the formulated feed enriched with spinach extract had a significant effect on absolute weight, specific growth rate, length, and width of the carapace in growth performance (P<0.05) but had no significant on the survival rate and the molting frequency (P>0.05). The best result was treatment A3, adding 0.5 g of spinach extract to lobster feed with absolute weight 39.67±6.20 g, length of carapace 0.46±0.06 cm, width of carapace 0.28±0.05 cm, specific growth rate 0.38±0.06% day-1, molting frequency 1.00±0.00 times lobster-1, and survival rate 100±0.00%. The Spinach extract of 0.5 mg was the best for the survival and growth of the lobster (Duncan's test). The chemical of the feed showed that the tested feed met the nutritional needs of lobsters with a protein content of 39.74-42.60%. However, the number of amino acids in the best test feeds was still low quantity compared to several other studies, so the growth of lobsters was still slow. Based on research results, enriched 0.5 g of spinach extract to formulated feed is the best result for increasing the growth and survival rate of lobsters.